The Extract of Crocus sativus and Its Constituent Safranal, Affect Serum Levels of Endothelin and Total Protein in Sensitized Guinea Pigs - Gholamnezhad, Zahra (Mashhad University of Medical Sciences, 2013)
Objective(s): The effect of the extract of Crocus sativus and its constituent, safranal on inflammatory markers in sensitized guinea pigs was examined. Materials and Methods: Ovalbumin (OA) sensitized guinea pigs were given drinking water alone (group S), or drinking water containing three concentrations of safranal, three concentrations of extract and one concentration of dexamethasone, (n=6, for all groups) and serum levels of endotheline-1 (ET-1) and total protein (TP) were assessed. Results: Serum levels of ET-1 and TP in group S were significantly higher than control group (P<0.01 for ET-1 and P<0.001 TP). Treatment of S animals with dexamethasone, most concentrations of the extract and safranal significantly reduced serum levels of ET-1 and TP compared to group S (P <0.01 to P <0.001). The effects of one concentration of the extract and safranal were significantly higher than dexamethasone (P <0.05 to P <0.01). Conclusion: A preventive effect of the extract of C. sativus and its constituent safranal on serum inflammatory markers in sensitized guinea pigs was shown.